Officiating ceremony and exhibition of Pahang Biodiversity- Biotechnology Research Centre of Excellence during Mini MAHA 2011 - M. M., Yusoff; Saifful Kamaluddin, Muzakir; Nurul Nadia, Abd Razak; Muhammad Najib, Muhammad Nor (Penerbit UMP, 2011)
Pahang Biodiversity-Biotechnology Research Cent re of Excellence which is sit uated at Sultan Haji Ahmad Shah Agricultural Park, Kuantan, has been officiated by KDYMM Sultan Pahang on 28th May 2011 in conjuct ion with Mini MAHA 2011.